Risk factors for vascular complications and treatment patterns at diagnosis of 2389 PV and ET patients: Real‐world data from the Swedish MPN Registry. (3rd April 2017) - Abdulkarim, Khadija; Samuelsson, Jan; Johansson, Peter; Andréasson, Björn
Abstract: Objective: The study mainly aimed at investigating possible correlations between peripheral blood counts, erythropoietin (EPO), JAK2 V617F mutation, and vascular complications prior to diagnosis of a population‐based cohort of newly diagnosed patients with myeloproliferative neoplasms (MPN). Method: The study comprises 1105 patients with polycythemia vera (PV) and 1284 patients with essential thrombocythemia (ET) registered in the Swedish MPN Registry. Results: Vascular complications, prior to diagnosis, were registered in 37% of PV patients. In multivariate analysis, low hemoglobin was the only significant risk factor ( P =.0120). Among ET patients, 35% had encountered a vascular complication. Risk factors for thromboembolic complications in ET were identified as age>65 years, white cell count>12×10 9 /L, and the presence of JAK2 V617F mutation ( P =.0004, P =.0038, and P =.0016, respectively). A JAK2 V617F mutation was present in 71% of ET patients with vascular complications, compared to 60% in patients without. A majority of complications were thromboembolic, in both PV and ET. Conclusion: We conclude that vascular complications among newly diagnosed patients had affected more than one‐third of our study population. Risk factors for vascular complications prior to diagnosis were lower hemoglobin in PV, and the presence of JAK2 V617F mutation, higher age, and leukocytosis in ET.